Biotechnology and fish culture - Foresti, F. (Kluwer Academic Publ, 2000)
Biotechnology can currently be considered of importance in aquaculture. The increase in the production of aquatic organisms over the last two decades through the use of biotechnology indicates that in a few generations biotechnology may overtake conventional techniques, at least for the commercially more valuable species. In the last few years, genetics has contributed greatly to fish culture through the application of the more recent techniques developed in biotechnology and in genetic engineering. At present, the most commonly used methods in fish biotechnology are chromosome manipulation and hormonal treatments, which can be used to produce triploid, tetraploid, haploid, gynogenetic and androgenetic fish. These result in the production of individuals and lineages of sterile, monosex or highly endogamic fish. The use of such strategies in fish culture has as a practical objective the control of precocious sexual maturation in certain species; other uses are the production of larger specimens by control of the reproductive process and the attainment of monosex lines containing only those individuals of greater commercial value. The use of new technologies, such as those involved in gene transfer in many species, can result in modified individuals of great interest to aquaculturists and play important roles in specific programmes of fish production in the near future.
Keywords: aquaculture; chromosome manipulation; ploidy